Convergent and Discriminant Validity of the Five Factor Form and the Sliderbar Inventory. (March 2018) - Rojas, Stephanie L.; Widiger, Thomas A.
Existing measures of the five factor model (FFM) of personality are generally, if not exclusively, unipolar in their assessment of maladaptive variants of the FFM domains. However, two recently developed measures, the Five Factor Form (FFF) and the Sliderbar Inventory (SI), include items that assess for maladaptive variants at both poles of each item. This structure is unique among existing measures of personality and personality disorder, although there is a historical, infrequently used Stone Personality Trait Schema (SPTS) that had also included this item structure. To facilitate an exploration of their convergent and discriminant validity, the SI and SPTS items were reorganized into FFM scales. The convergent and discriminant validity of the FFF, SI-FFM, and SPTS-FFM scales was considered in a sample of 450 adults with current or a history of mental health treatment. The FFF, SI-FFM, and SPTS-FFM were also compared with respect to their relationship with FFM domains. Finally, the FFF items and SI-FFM scales were tested with respect to their relationship with measures of maladaptive variants of both high and low agreeableness and conscientiousness. The implications of the results are discussed with respect to the assessment of maladaptive personality functioning, and suggestions for future research are provided.